2012
DOI: 10.1002/job.1781
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of mentor and protégé outcomes in formal mentoring relationships

Abstract: Summary This study examined relationships between mentoring functions offered and transformational leadership as a mentor outcome and affective well‐being and organizational commitment as mutual outcomes for both mentors and protégés. For this examination, we conducted a longitudinal field study by using 111 matched reports from both mentors and protégés collected at three different points in time over seven months in nine Korean companies that administered a standardized formal mentoring program. Study result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 85 publications
3
121
0
1
Order By: Relevance
“…Ragins et al [63] demonstrated that protégés experience a greater level of organizational commitment compared to non-mentored employees. Chun et al [64] identified affective well being and organizational commitment as mutual outcomes of the mentoring relationship. Hartmann et al [65] posited in detail that mentoring is positively associated with protégés' affective and normative organizational commitment.…”
Section: Managerial Coaching Mentoring and Organizational Commitmentmentioning
confidence: 99%
“…Ragins et al [63] demonstrated that protégés experience a greater level of organizational commitment compared to non-mentored employees. Chun et al [64] identified affective well being and organizational commitment as mutual outcomes of the mentoring relationship. Hartmann et al [65] posited in detail that mentoring is positively associated with protégés' affective and normative organizational commitment.…”
Section: Managerial Coaching Mentoring and Organizational Commitmentmentioning
confidence: 99%
“…From 2007 to the present we have continued to apply the model in our own mentorship of novice teachers during their extended-practicum programs, and we have also been more widely distributing the model through public presentations and scholarly publications (Ralph & Walker, 2011a, 2012. As a result of these dissemination efforts, leaders from several other professional disciplines have implemented the AM model.…”
Section: Results From a Variety Of Professionsmentioning
confidence: 99%
“…Some of the mentorship research has indicated that although the relationship between mentors and protégés is typically positive (Chun, Sosik, & Yun, 2012), there is in many cases a deficiency that arises within the mentorship transaction. The problem may emerge from inadequate/inappropriate guidance, unacceptable supervisory interventions, unproductive mentoring responses, or poor leader communication (Taherian & Shekarchian, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…389-390). Desimone, Hochberg, Porter, Polikoff, Schwartz and Johnson (2014) ;Chun, Sosik and Yun (2012) and Ragins and Cotton (1999) concur that the occupational environment is an important factor when examining the effectiveness of mentoring. They claim, however, that even more essential is the examination of informal and formal mentoring, separately, within work settings.…”
Section: Role Models and Mentorsmentioning
confidence: 90%